Human immunodeficiency virus associated tuberculosis more often due to recent infection than reactivation of latent infection [Review article] - Houben, Rein M. G. J.; Crampin, A. C.; Ndhlovu, R.; Sonnenberg, P.; Godfrey-Faussett, P.; Haas, W. H.; Engelmann, Guido; Lombard, C. J.; Wilkinson, D.; Bruchfeld, J.; Lockman, S.; Tappero, J.; et al. (The international journal of tuberculosis and lung disease, 2011)
BACKGROUND: It is unclear whether human immunodeficiency virus (HIV) increases the risk of tuberculosis (TB) mainly through reactivation or following recent Mycobacterium tuberculosis (re)infection. Within a DNA fingerprint-defined cluster of TB cases, reactivation cases are assumed to be the source of infection for subsequent secondary cases. As HIV-positive TB cases are less likely to be source cases, equal or higher clustering in HIV-positives would suggest that HIV mainly increases the risk of TB following recent infection.METHODS: A systematic review was conducted to identify all studies on TB clustering and HIV infection in HIV-endemic populations. Available individual patient data from eligible studies were pooled to analyse the association between clustering and HIV.RESULTS: Of seven eligible studies, six contributed individual patient data on 2116 patients. Clustering was as, or more, likely in the HIV-positive population, both overall (summary OR 1.26, 95%CI 1.0-1.5), and within age groups (OR 1.50, 95%CI 0.9-2.3; OR 1.00, 95%CI 0.8-1.3 and OR 2.57, 95%CI 1.4-5.7) for ages 15-25, 26-50 and >50 years, respectively.CONCLUSIONS: Our results suggest that HIV infection mainly increases the risk of TB following recent M. tuberculosis transmission, and that TB control measures in HIV-endemic settings should therefore focus on controlling M. tuberculosis transmission rather than treating individuals with latent M. tuberculosis infection.